Proceedings of the 4th ACM International Workshop on Contents Protection and Security 2006
DOI: 10.1145/1178766.1178769
|View full text |Cite
|
Sign up to set email alerts
|

Sharing digital rights with domain licensing

Abstract: Sharing of multimedia content is a common practice that, combined with appropriate business models, need not be detrimental to the interests of content providers. Existing digital rights management systems, however, support only relatively limited sharing of content between multimedia terminals, resulting in inconvenience and frustration for end-users of rights-managed content. In this paper, we propose to combine the notion of an "authorised domain" with an "environment role" to permit end-users to share acce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 17 publications
(15 reference statements)
0
8
0
Order By: Relevance
“…This is the classic DRM solution for content sharing, in which a group of authorized devices are defined as belonging to a joint domain, and devices within the same domain can freely share content between them. The studies [4,5] suggest improvements in the authorized domain model. Other studies do not assume that model: Sadeghi et al [6] provide a secure platform on open systems which allows the usage of dynamic licenses; Lee et al [7] propose a system for content sharing which relies on time-based rights.…”
Section: Related Work and Content Sharing With Proxy Re-encryptionmentioning
confidence: 99%
“…This is the classic DRM solution for content sharing, in which a group of authorized devices are defined as belonging to a joint domain, and devices within the same domain can freely share content between them. The studies [4,5] suggest improvements in the authorized domain model. Other studies do not assume that model: Sadeghi et al [6] provide a secure platform on open systems which allows the usage of dynamic licenses; Lee et al [7] propose a system for content sharing which relies on time-based rights.…”
Section: Related Work and Content Sharing With Proxy Re-encryptionmentioning
confidence: 99%
“…Other systems use the licence issuer as the domain controller [84], so that the rights-holder is able to determine directly what devices should be members of a domain. Some more recent authors have suggested that membership be controlled by some machine-readable policy transmitted from the rights-holder to the domain controller [72,101,77].…”
Section: Authorised Domainsmentioning
confidence: 99%
“…At the moment the definitions of the domains are too connected to the physical world (a typical domain, for example, consists of the devices within one household or belonging to a single user [7]). The most popular approaches define a domain by the use of three primitivescardinality (a device can become a valid member of the domain if the overall number of devices in the domain does not exceed a given limit), time-outs (the membership in the domain is withdrawn after a certain time forcing the device to re-authorize), and proximity (confirms that the device is in a close range of the "domain holder").…”
Section: Introductionmentioning
confidence: 99%